Notes on "The Sick Face" of Isidoro and Florencio Monje Gil - Francisco Herrera-Rodríguez (Universidad de Alicante, 2017)
In this review, the author describes and analyzes the contents of the book "The sick face" highlighting its great pertinence as a source for the history of medicine.